PENGARUH TINGKAT KECERDASAN EMOSI, KEPUASAN KERJA DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PEGAWAI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN SERDANG BEDAGAI - Nelson Pinem (Manajemen dan Bisnis, 2019)
The formulation of the problem in this research is how the effect of emotional intelligence level, job satisfaction and organizational culture partially or simultaneously toward Organizational Citizenship Behavior (OCB) of Staff Sekretariat Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten Serdang Bedagai. This research aims to determine and analyze the effect of emotional intelligence level, job satisfaction and organizational culture on Organizational Citizenship Behavior (OCB) of Staff Sekretariat Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten Serdang Bedagai either partially or simultaneously.The method of analysis used in this research is descriptive data analysis  and then analyzed by using multiple linier regression. The variables in this research are the  emotional intelligence level, job satisfaction and organizational culture as independent variables and organizational citizenship behavior (OCB) as dependent variable. The sample used in this research is 30 people. The results showed partially variable emotional intelligence level have a positive and significant effect on Organizational Citizenship Behavior (OCB), variable of job satisfaction have a positive and significant effect on Organizational Citizenship Behavior (OCB) and variable of organizational culture have  a positive and significant effect on Organizational Citizenship Behavior (OCB). Simultaneously variables emotional inteligence level, job satisfaction and organizational culture have an effect on on Organizational Citizenship Behavior (OCB) equel 11,176 and significance value 0,000. The value of R Square is 0,563. This shows that 56,3% organizational citizenship behavior (OCB)  of Staff Sekretariat Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten Serdang Bedagai can be explained by the variables level emotional intelligence, job satisfaction and organizational culture, while the rest 43,7% not done research. Keywords : Emotional Intelligence, Job Satisfaction, Organizational Culture, OCB